The Effect of Corporate Governance, Profitability, and Working Capital on Carbon Emission Disclosure in Energy Sector Companies - Hazna Puspa Primalia, Mariezka; Eko Prasetio, Januar (Dinasti Publisher, 2025)
The purpose of this research is to empirically prove the influence of corporate governance, profitability, and working capital on carbon emission disclosure. The population used in this study consists of energy sector companies listed on the Indonesian Stock Exchange from 2020 to 2023. The sampling was conducted using purposive sampling with predetermined criteria, resulting in 139 data points. The results of this study indicate that corporate governance affects carbon emission disclosure. Meanwhile, profitability and working capital don’t affect carbon emission disclosure